Various treatment options of early carcinoma buccal mucosa involving commissure: a tertiary care centre experience of six years - Shanmugam, Subbiah; Susikar, Sujay; Hussain, Syed Afroze; Robert, Kenny (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Carcinoma of the buccal mucosa is the most common cancer of the oral cavity in India and involvement of commissure poses unique challenge in reconstruction after surgery. Aim was to analyse the demographics, presentations and various treatment options of early carcinoma buccal mucosa involving oral commissure. Methods: A retrospective review from clinical case records at our institution between 2014 and 2019 were analysed. All the cases recruited were analysed based on patient characteristics, clinical presentation, surgical and adjuvant therapy rendered. Statistical analysis was done using SPSS 20 software. Results: A total of 40 patients of primary carcinoma buccal mucosa with T1 to T3 disease involving commissure were analysed. Median age of presentation was 51 years with male preponderance (24:16). 32 patients were offered surgery as the initial line of management and 8 received definitive radiotherapy. The estimated 5-year survival was around 30%. Two patients with clinically T2 disease were upstaged in the postoperative histopathology to T3 and T4a respectively one due to depth of invasion >10 mm and the other owing to commissural skin involvement detected only in the final HPE. Conclusions: Early carcinoma of the buccal mucosa clinically extending from commissure poses unique challenges in choosing treatment modalities. In view of the location of the tumour it poses a small chance of upstaging of early disease in the final histopathology.